Macrophage Immunomodulation Through New Polymers that Recapitulate Functional Effects of Itaconate as a Power House of Innate Immunity. (13th November 2020) - Davenport Huyer, Locke; Mandla, Serena; Wang, Yufeng; Campbell, Scott B.; Yee, Bess; Euler, Christian; Lai, Benjamin F.; Bannerman, A. Dawn; Lin, Dawn S. Y.; Montgomery, Miles; Nemr, Kayla; Bender, Timothy; et al.
Abstract: Itaconate (ITA) is an emerging powerhouse of innate immunity with therapeutic potential that is limited in its ability to be administered in a soluble form. A library of polyester materials that incorporate ITA into polymer backbones resulting in materials with inherent immunoregulatory behavior is developed. Harnessing hydrolytic degradation release from polyester backbones, ITA polymers result in the mechanism specific immunoregulatory properties on macrophage polarization in vitro. In a functional assay, the polymer‐released ITA inhibits bacterial growth on acetate. Translation to an in vivo model of biomaterial associated inflammation, intraperitoneal injection of ITA polymers demonstrate a rapid resolution of inflammation in comparison to a control polymer silicone, demonstrating the value of sustained biomimetic presentation of ITA. Abstract : Harnessing the power of innate immunity, a family of degradable polyester materials is developed that recapitulate the functional effects of itaconate in a sustained delivery. Synthesized through a one pot condensation, hydrolytic degradation molecule release from itaconate polymer backbones regulates inflammation in local cellular microenvironments in a biomimetic fashion.